Husain-Usmani Model for Grief Truncation Acronym “Seeding of Solace” (SOS): An Integrated Approach - Husain, Munawwar; Usmani , Javed Ahmad (Journal of Indian Academy of Forensic Medicine, 2015)
There are various situations that require consolation for the bereaved. Each one of the situation demands special task to be effective. This study focuses exclusively on grief counselling of the bereaved restricted to the mortuary. It is the culmination of decades of cumulative experience of the authors in dealing with myriad complexities associated with autopsy, the thin line of balance required to be maintained with confidentiality and disclosure, and at the same time discharging the task of counselling in a highly charged atmosphere some time bordering rebellion. An attempt has been made to construct a model named “Husain-Usmani Model for Grief Truncation acronym „Seeding of Solace‟ (SOS). It is hoped that by following this model some level of amelioration of grief could be achieved and the situation could be saved from getting worse aptly a distress call SOS - Save Our Soul. At the same time it is advised that personal discretion is required tantamount to situational freaks because no two situations are alike.